Uso da PCR para monitoramento das espécies de Biomphalaria e da taxa de infecção pelo Schistosoma mansoni em molusco na região do Sul de Minas Gerais - Gomes, Amanda Ribas (2015)
Schistosomiasis is a parasitic disease, chronic, debilitating and lethal in some cases. It is endemic in tropical and subtropical countries and affects individuals in rural areas. Around 779 million people live in endemic areas and are at risk of infection. Fifty percent of infected patients are symptomatic and less than 20 million have severe manifestations of the disease. Its main vectors snails belong to Planorbidae family, which includes genus Biomphalaria and comprises three species of Schistosoma mansoni vectors in Brazil: Biomphalaria glabrata, Biomphalaria tenagophila and B. straminea. Morphological identification of freshwater molluscs with medical importance is very complicated due the large intra-specific variations in morphological characteristics used in classical identification. In order to solve this problem, molecular biology techniques were used as additional tools for the identification of these molluscs. PCR has been successfully used as a specific, sensitive and rapid detection of pathogens in water, soil and food. Therefore, this study aimed to use PCR to confirm the identity and search for parasites in vectors of schistosomiasis in the cities of south Minas Gerais. These cities are considered risk areas due to the presence of both intermediate hosts and carriers of the disease coming from other regions of the state or country. PCR was able to demonstrate the presence of Biomphalaria tenagophila guaibenses snails in the city of Arceburgo, which presented two infected samples, and non-infected samples Biomphalaria peregrina snails in the city of Fama. The presence of infection probably occurs due to the migration of individuals, who come to work in sugarcane and coffee plantations, from endemic areas to the study area,. The occurrence of new infected vectors increases the necessity for control and surveillance of schistosomiasis in the region.